The Influence of Product Quality, Price and Promotion on T-Shirt Purchasing Decisions at Arei Store Bogor - Dwi Gemina; Nur Muhammad Rizqi; Rachmat Gunawan (West Science Interdisciplinary Studies, 2024)
This research aims to determine and analyze the influence of product quality, price and promotion on purchasing decisions, both simultaneously and partially. This research design uses descriptive, verification and path analysis research methods. The sampling technique uses the saturated sampling method. The number of respondents was 100 people. The subjects of this research are consumers of Arei Store Bogor, and the objects of research are product quality, price, promotions and purchasing decisions. The tools used in this analysis are path analysis, multiple correlation analysis, coefficient of determination analysis, and hypothesis testing (F test and t test). The results of the analysis show that partially or simultaneously product quality, price and promotion have a direct and positive influence on purchasing decisions at Arei Store Bogor.